Case Report: Acquired Haemophilia A Following mRNA-1273 Booster Vaccination Against SARS-CoV-2 With Concurrent Diagnosis of Pleomorphic Dermal Sarcoma - Plüß, Marlene; Mitteldorf, Christina; Szuszies, Christoph Johannes; Tampe, Björn (Frontiers in Immunology, 2022)
While the global pandemic caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is still ongoing and new virus variants are emerging, there is a universal need for vaccines to protect individuals from severe complications and ideally control the pandemic by enabling herd immunity. Several vaccines against SARS-CoV-2 have been approved and are widely used to stem the recurring waves of coronavirus disease 2019 (COVID-19). Post-marketing surveillance is essential to record even rare safety issues related to these new vaccines. Among these issues, several autoimmune phenomena have been recorded in temporal association with and feasibly triggered by a vaccination. Acquired haemophilia A (AHA) is a rare condition characterized by new-onset haemorrhagic diathesis caused by an inhibitor of blood clotting factor VIII (FVIII), often in the elderly and most commonly associated with autoimmune or malignant disease. There have been a small number of AHA cases triggered by vaccinations, including those against SARS-CoV-2. We report the first case of AHA in temporal association with an mRNA-1273 booster vaccination. The diagnosis was made promptly, and the patient received appropriate care including immunosuppression using glucocorticoids, cyclophosphamide (CYC) and rituximab (RTX). The haemorrhage ceased after escalation of treatment, and the patient is recovering. Concurrent malignancy was initially ruled out using a wide scope of diagnostic tests, but pleomorphic dermal sarcoma (PDS) of the forehead occurred after initiation of specific AHA immunosuppressive treatment. Since large vaccination programs are ongoing worldwide and potential adverse events during post-marketing surveillance have been reported following vaccination against SARS-CoV-2, this case illustrates challenges in rare events occurring in association with SARS-CoV-2 vaccination and to proof a causal relationship. Therefore, there is an urgent need for reporting any events in association with SARS-CoV-2 vaccination, but also a crucial discussion about possible concurrent triggers and follow-up information about individual patients.